El valor histórico del pituto: Clase media, integración y diferenciación social en Chile - Barozet, Emmanuelle (Revista de Sociología, 2006)
This article deals with a practice deeply rooted in the social life of the Chilean middle class : the exchange of favors which, through reciprocity and friendship ties, insures access to diverse types of goods and services. A large array of socio-historical analyses has established that this form of organic solidarity finds its social origins in the very formation of the middle class at the turn of the Twentieth century. I argue here, however, that this practice was affected by macro-sociological processes of social change that significantly transformed it in the course of the following decades. The article describes, analyzes and explains reciprocity through a double historical and sociological lense, examining the various logics at work in this form of social solidarity.